Rapid Staphylococcus aureus Detection From Clinical Mastitis Milk by Colloidal Gold Nanoparticle-Based Immunochromatographic Strips - Nagasawa, Yuya; Kiku, Yoshio; Sugawara, Kazue; Yabusaki, Naohiro; Oono, Kazuyoshi; Fujii, Kento; Suzuki, Takahide; Maehana, Koji; Hayashi, Tomohito (Frontiers in Veterinary Science, 2020)
Rapid diagnostic technologies for bovine mastitis caused by Staphylococcus aureus (S. aureus) are urgently needed. In the current study, we generated an anti-ribosomal protein-L7/L12 antibody to detect S. aureus and an anti-ribosomal protein-L7/L12 antibody-coated immune-chromatographic strip (ICS) test. Moreover, we determined the ability of the ICS test to detect S. aureus from milk samples collected from cows with clinical mastitis. The developed ICS reacted to S. aureus in a bacteria load-dependent manner with a detection limit of ~104 CFU/mL. In the evaluation of possible cross-reactivity of the ICS test, six strains of coagulase-negative Staphylococci showed slightly positive reactions, although at a lower level; however, other bacteria were completely negative. Next, we investigated the sensitivity and specificity of the ICS test compared with the bacteriological culture method using milk samples from clinical bovine mastitis. The results of the experiments demonstrated that the ICS test had high sensitivity [100%, 95% confidence interval (CI): 91.3–100%] and specificity (91.9%, CI: 90.5–91.9%) compared with culture tests. In addition, the kappa statistic demonstrated that ICS tests showed substantial agreement (k = 0.77, CI: 0.66–0.87) with culture tests. Positive correlations were observed for the statistical analysis between S. aureus (nuc gene) copy numbers and ICS test scores in mastitic milk infected by S. aureus. Therefore, we assume that this new detection method using ICS may be useful as a highly sensitive S. aureus-screening method for the diagnosis of bovine mastitis. Our findings support the ongoing effort to develop an ICS method for bovine S. aureus-induced mastitis, which can contribute to the rapid diagnosis of this disease.